Pharmacokinetics, protein binding, and metabolism of a quinoxaline urea analog as a NF-кB inhibitor in mice and rats by LC-MS/MS - Gautam, Nagsen (2013)
13–197 is a novel NF-ĸB inhibitor that shows promising in-vitro efficacy data against pancreatic cancer. In this study, we characterized the pharmacokinetics (PK), tissue distribution, protein binding, and metabolism of 13–197 in mice and rats. A valid, sensitive, and selective LC-MS/MS method was developed. This method was validated for the quantification of 13–197, in the range of 0.1–500 ng/ml in mouse plasma, liver, kidney, lung, heart, spleen, brain, urine and feces. 13–197 has low bioavailability of 3 and 16% in mice, and rats respectively. 13–197 has faster absorption in mice with 12-fold shorter T(max) than in rats. Tissue concentrations were 1.3–69.2 folds higher in mice than in rats at 72h after intravenous administration. 13–197 is well distributed to the peripheral tissues and has relatively high tissue: plasma concentration ratios, ranging from 1.8 to 3634, in both mice and rats. 13–197 also demonstrated more than 99% binding to plasma proteins in both mice and rats. Finally, less than 1% of 13–197 is excreted unchanged in urine and feces, and metabolite profiling studies detected more than 20 metabolites in mice and rats plasma, urine, and feces, which indicates 13–197 is extensively metabolized and primarily eliminated by metabolism rather than by excretion.